2022
DOI: 10.1007/s40211-022-00438-9
|View full text |Cite
|
Sign up to set email alerts
|

Die psychische Gesundheit unserer Kinder und Jugendlichen und deren Behandlungsmöglichkeiten im Drei-Länder-Vergleich (Ö, D, CH) unter Berücksichtigung der Veränderungen durch die COVID-19-Pandemie

Abstract: Zusammenfassung Hintergrund und Fragestellung In einer von der Österreichischen Gesellschaft für Kinder- und Jugendpsychiatrie, Psychosomatik und Psychotherapie (ÖGKJP) für die Neuropsychiatrie kuratierten Artikelserie erscheinen in einem Schwerpunktheft Arbeiten, die die kinder- und jugendpsychiatrische Versorgungslage zum Thema haben. Der vorliegende Artikel hat sich zum Ziel gesetzt, einen diesbezüglichen Drei-Länder-Vergleich zwischen Österreich, Deutschland und der Schweiz zu m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
2
0
2
Order By: Relevance
“…Geweniger et al [73] found a strong association between parent-reported child mental health problems and pandemic-related variables, such as increased family conflict, inadequate social support, and caregivers' mental health. Similar observations were made in German-speaking countries (Austria, Germany, Liechtenstein, and Switzerland), where a substantial proportion of children and adolescents experienced pandemic-related mental health problems [74][75][76]. In Italy, depression in children was found to be dependent on parental stress [77].…”
Section: Discussionsupporting
confidence: 73%
“…Geweniger et al [73] found a strong association between parent-reported child mental health problems and pandemic-related variables, such as increased family conflict, inadequate social support, and caregivers' mental health. Similar observations were made in German-speaking countries (Austria, Germany, Liechtenstein, and Switzerland), where a substantial proportion of children and adolescents experienced pandemic-related mental health problems [74][75][76]. In Italy, depression in children was found to be dependent on parental stress [77].…”
Section: Discussionsupporting
confidence: 73%
“…About one third of girls and one fifth of boys suffer from multiple psychosomatic complaints in Germany [13,14]. Impairments in subjective well-being manifest themselves mainly in girls, older adolescents, and young people with less family prosperity and high levels of school stress.…”
Section: Introductionmentioning
confidence: 99%
“…Impairments in subjective well-being manifest themselves mainly in girls, older adolescents, and young people with less family prosperity and high levels of school stress. Strong family support is associated with better subjective wellbeing [13]. A hospital stay means an additional stress factor for chronically ill children and adolescents [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Diese Strategie wird von vielen Kliniken bereits intensiv verfolgt. Jedoch werden Fachärzte für Kinder- und Jugendpsychiatrie nicht nur in Deutschland, sondern im gesamten deutschsprachigen Raum dringend gesucht: Insbesondere in Österreich ist es angesichts einer (im Vergleich zu Deutschland) noch sehr jungen fachärztlichen Disziplin [ 39 , 40 ], die sich in einem massiven Ausbau befindet [ 41 , 42 ], kaum möglich, diesen Aufbau mithilfe der eigenen Ressourcen zu bewerkstelligen, so dass auch hier starke Rekrutierungsbemühungen für Ärzte aus dem Ausland bestehen, was die prekäre personelle Lage unterstreicht [ 43 , 44 ]. Pro: Durch diesen Schritt ließen sich schnell neue Kapazitäten schaffen.…”
Section: Mögliche Handlungsoptionenunclassified